Autonomous RC Hospital Smart Bed for Accident Patients - N. Ashwini, S. Vimala (International Journal of Advanced Science and Technology, 2020)
This paper is to develop a prototype of an autonomous RC(Remote Control) hospital bed controlled by IoT. The RC hospital bed has four wheels on which front wheels help the RC hospital bed to turn in the right or left direction with the back wheels help the RC to move forward and backward. The ultrasonic sensor is attached at the front of the RC hospital bed to detect the obstacles when passing through them.  A 2 lane track has built to test the RC hospital bed. The bed can navigate itself through the path as well as if any barrier where observed it stops moving and produces an alert sound.  By using a smartphone application we can control the smart bed. When a button is a press down in the application, the command data will send to the smart bed with the help of a wifi module to control the movement of the RC hospital smart bed.